An Efficient One‐Pot Four‐Component Synthesis of Functionalized Imidazo[1, 2‐a]pyridines. Issue 3 (13th March 2013) - Kazemi Movahed, Siyavash; Dabiri, Minoo; Bazgir, Ayoob
Abstract An efficient one‐pot four‐component protocol for the synthesis of imidazo[1, 2‐a]pyridines was developed by condensing ethane‐1, 2‐diamine (2), 1, 1‐bis(methylthio)‐2‐nitroethene (1), aldehydes 3, and activated methylene compounds in EtOH under reflux conditions (Tables 1–3). The features of this procedure are operational simplicity, good yields of products, in situ preparation of heterocyclic ketene aminals (HKA), and catalyst‐free conditions.